السمع والطاعة في الإسلام: دراسة أوّلية - Misnawati, Misnawati; Elatrash, Radwan Jamal Yousef (Universitas Islam Negeri Ar-Raniry, 2022)
This research deals with a preliminary study for hearing and obedience in Islam. These two words are often mentioned together in the Holy Qur’an. A good Muslim must have a solid commitment to apply both in his daily life. This research aims to explain the concept of hearing and obedience; report the importance of hearing and obedience; explain the types of hearing and obedience, and discover the effects of hearing and obedience both individually and collectively. In this study, the researcher used the thematic method by displaying verses of the Qur'an or the hadīths of the Prophet related to the word of hearing and obedience. Then summarizes that hearing and obedience to Allāh  and the Messenger of Allāh  is absolute. As for hearing and obedience to guardians, parents, the husband, and others, they are restricted to what was known in the Sharia, that is, if they agree to the truth and what violate, meaning as long as they are not commanded to disobey Allāh, because there is no obedience to a created being in disobedience to the Creator. He who is characterized by this quality has thoroughly enjoyed this life and the hereafter. Hearing and obedience have consequences on the individual level: obtaining the mercy of God Almighty, God’s love and forgiveness, victory and success, guidance, tranquility, and the blessing of feasting with the prophets, martyrs, and righteous people in heaven. As for the effects on the collective level, they are the achievement of coalition and meeting and highlighting the identity of the Muslim Ummah. Penelitian ini berkaitan dengan studi pendahuluan tentang al sam'u wa al tā'ah dalam Islam. Kedua kata ini sering disebutkan secara beriringan dalam al Qur`an. Seorang muslim yang baik harus memiliki komitmen yang kuat untuk mengaplikasikan keduanya dalam kehidupan kesehariannya. Penelitian ini bertujuan untuk menjelaskan maksud dari al sam'u wa al tā'ah dan pentingnya al sam'u wa al tā'ah serta jenis-jenis al sam'u wa al ṭā'ah. Kemudian juga untuk mengungkapkan pengaruh al sam`u wa al ṭā'ah baik secara individu maupun secara berkelompok. Dalam penelitian ini penulis menggunakan metode tematik dengan menampilkan ayat-ayat al Qur`an atau hadith- hadith Nabi yang terkait dengan kata al sam'u wa al ṭā'ah. Hasilnya menunjukkan bahwa al sam'u wa al ṭā'ah kepada Allah dan Rasul adalah sesuatu yang mutlak. Sedangkan al sam'u wa al tā'ah kepada ūlī al Amri, orang tua, suami dan selain mereka dibatasi oleh hal-hal yang menurut syara' baik dan selama mereka tidak menyuruh untuk berbuat maksiat kepada Allah. Karena tidak ada ketaatan kepada makhluk dengan melakukan maksiat kepada Khāliq. Orang yang mempunyai sifat ini maka sungguh ia sudah dapat menikmati kehidupan dunia dan akhirat dengan sempurna. Al sam'u wa al tā'ah memiliki pengaruh pada tingkat individu, yaitu memperoleh rahmat Tuhan Yang Maha Esa, cinta dan pengampunan Tuhan, kemenangan kesuksesan, bimbingan, serta nikmat kebersamaan dengan para nabi, syuhada dan orang-orang saleh di surga. Adapun efeknya pada level kolektif adalah tercapainya koalisi dan pertemuan, serta penonjolan identitas umat Islam. يتناول هذا البحث دراسة أولية للسمع والطاعة في الإسلام. ولفظ السمع مقرونًا بلفظ الطاعة غالبًا في القرآن الكريم. يجب على المسلم أن يكون لديه التزام قوي لتطبيقهما في حياته اليومية. يحاول هذا البحث توضيح مفهوم السمع والطاعة وبيان أهميتهما وأنواعهما. ثم اكتشاف الآثار المترتبة على السمع والطاعة سواء كان على المستوى الفردي أو على المستوى الجماعي. استخدمت الباحثة في هذه الدراسة المنهج الموضوعي من خلال عرض الآيات القرآنية أو الأحاديث النبوية المتعلقة بالسمع والطاعة. ويلخص إلى أن مطلقة، أما  كلمة السمع في القرآن الكريم ما زالت متّبعة إلى الطاعة. إن السمع والطاعة وللرسول السمع والطاعة لأولي الأمر والوالدين والزوج وغيرهم فمقيدة بما كانت معروفًا في الشرع أي إذا وافقوا الحق وما خالفوه بمعنى ما دام لم يأمروا بمعصية لله، لأنه لا طاعة للمخلوق في معصية الخالق. ومن يتصف ذه الصفة فقد تمتع بالحياة الدنيا والآخرة كاملا . السمع والطاعة لهما آثار مترتبة على المستوى الفردي وهي حصول على رحمة لله تعالى، ومحبة لله ومغفرته، والفوز والفلاح، والهداية، والرشد، والسكينة، ونعمة المعيّة مع النبيين والشهداء والصالحين في الجنة. أما الآثار المترتبة على المستوى الجماعي فهي تحقيق الائتلاف والاجتماع، وإبراز هُويّة الأمة المسلمة. الكلمات الرئيسيّة: السمع؛ الطاعة؛ دراسة